Asymmetric Warfare: A State vs Non-State Conflict (2014)
Asymmetry in warfare is not a new phenomenon. Historically, it has been observed that on various occasions there has been a marked difference in the relative military power and strategy of the warring states. However, in the post 9/11 era, it has been observed that the character and nature of war itself is changing particularly amid the wars between state and non-state actors. The usage of unconventional tools and tactics, be it guerrilla warfare or terrorism or irregular warfare or any other forms are becoming more synonymous with non-state entities. All this is leading to a composition of warfare in which a non-state actor is using asymmetric methods to target the state’s vulnerabilities to achieve disproportionate effect. This paper debates the notion of Asymmetric Warfare, the characters of actors involved and the nature of the state’s response in the 21st century.